Non-binding relationship between visual features - Rangelov, Dragan; Zeki, Semir (Frontiers in Human Neuroscience, 2014)
The answer as to how visual attributes processed in different brain loci at different speeds are bound together to give us our unitary experience of the visual world remains unknown. In this study we investigated whether bound representations arise, as commonly assumed, through physiological interactions between cells in the visual areas. In a focal attentional task in which correct responses from either bound or unbound representations were possible, participants discriminated the colour or orientation of briefly presented single bars. On the assumption that representations of the two attributes are bound, the accuracy of reporting the colour and orientation should co-vary. By contrast, if the attributes are not mandatorily bound, the accuracy of reporting the two attributes should be independent. The results of our psychophysical studies reported here supported the latter, non-binding, relationship between visual features, suggesting that binding does not necessarily occur even under focal attention. We propose a task-contingent binding mechanism, postulating that binding occurs at late, post-perceptual, stages through the intervention of memory.